2022
DOI: 10.1177/19714009221122250
|View full text |Cite
|
Sign up to set email alerts
|

Practical microscopic neuroanatomy of the limbic system and basal forebrain identifiable on clinical 3T MRI

Abstract: Microscopic neuroanatomy of limbic system and basal forebrain on MRI is complex and is a terra incognita for many radiologists, clinicians, and neuroscientists. Interestingly, most of the important structures/at least anatomical regions containing these structures demonstrable on cadaveric and surgical dissections can be identified on clinical MRI, with 3T being much better than 1.5T. This article teaches the practical MRI identification of these structures which will greatly help in evaluating complex ailment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Using the convulsant toxin pentylenetetrazole in animal models was helpful in recognizing the role of MTT and MB as an important pathway in seizure propagation to the thalamic anterior nucleus and frontal cortex. 1,2 On MRI, the MTT can be identified on axial and coronal T2-weighted sequences as thin craniocaudally…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the convulsant toxin pentylenetetrazole in animal models was helpful in recognizing the role of MTT and MB as an important pathway in seizure propagation to the thalamic anterior nucleus and frontal cortex. 1,2 On MRI, the MTT can be identified on axial and coronal T2-weighted sequences as thin craniocaudally…”
Section: Discussionmentioning
confidence: 99%
“…The Papez' circuit is a closed cerebral neural circuit, starting from the hippocampus, then coursing through the fornix, mammillary body (MB), MTT, anterior nucleus of the thalamus (ATN), cingulum, entorhinal cortex/parahippocampal gyrus then back to hippocampus 1 . It was reported that the circuit is associated with learning, memory, and emotion functions as well as seizure activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations